Comparing the fate of antibiotic resistance genes in two full-scale thermophilic anaerobic digestion plants treating food wastewater. (September 2020) - Jang, Hyun Min; Lee, Jangwoo; Shin, Seung Gu; Shin, Jingyeong; Kim, Young Mo
Graphical abstract: Highlights: Fates of ARGs and intI 1 to full-scale thermophilic AD of FWW were investigated. Two-stage (acidogenic-methanogenic) AD showed effective removal of ARGs and intI 1. Most targeted ARGs showed a significantly positive correlation with intI 1. ARGs were driven by the interplay of various factors in full-scale AD of FWW. Abstract: This study focus on the fate of ARGs in the full-scale AD of food wastewater (FWW). Residue was collected from two different full-scale thermophilic AD treating FWW. Ten selected ARGs, including tetracycline resistance genes ( tet M, tet X, tet Q, tet H and tet G), sulfonamide resistance genes ( sul 1 and sul 2), quinolone resistance genes ( qnr D) and macrolide resistance genes ( erm B and erm C), were amplified using quantitative polymerase chain reaction (qPCR). Furthermore, the class 1 integron-integrase gene ( intI 1) was selected as a representative mobile gene element. Remarkable reduction in the ARGs and intI 1 was observed in two-stage (acidogenic–methanogenic) AD, particularly, tet G, tet H, tet M, tet Q, tet X and intI 1 not detected. Additionally, significant positive correlation ( p < 0.01) between ARGs and intI 1 suggested a strong likelihood of horizontal gene transfer (HGT). Furthermore, stepwise multiple linear regression analysis revealed significant factors related to the fate of individual ARGs and intI 1 during AD.